Cytokinetic bridge triggers de novo lumen formation in vivo - L. I. Rathbun (Nature Portfolio, 2020)
De novo lumen formation during vertebrate left–right organizer development is required for body axis establishment. Here the authors utilize zebrafish to demonstrate that the position and cleavage of the cytokinetic bridge in dividing left-right organizer cells dictates tissue morphogenesis.